Antibiotic resistance of Escherichia coli isolated from broiler farms in Medan and Deli Serdang Regency - Sirindon, Madhumita; Julianti, Elisa; Faisal, Faisal; Putra, Desriwan Angga (The International Journal of Tropical Veterinary and Biomedical Research, 2024)
Antimicrobial Resistance (AMR) is the ability of microbes to inhibit treatment effects triggered by overuse and inappropriate use of antibiotics in poultry farms. This study aims to get an overview of the risk factors of AMR. A total of 41 E. coli isolated from caecum in poultry slaughterhouses derived from broiler chicken farms in Medan and Deli Serdang. The sample was tested for AMR using the Microbroth Dilution technique (Sensititre Microplate) with standards CLSI VET01S (2015) and CLSI M100. Information on risk factors was taken from farms using a questionnaire and analyzed with a logistic regression model (EPI Info 7 CDC). The result for sensitivity to 13 types of antibiotics showed that Trimethoprim had the highest resistance (95.1%), followed by ampicillin (90.2%), gentamicin (87.8%), nalidixide acid (85.4%), cefotaxime (82.9%), and sulfamethoxazole (82.9%). In contrast, colistin and meropenem have not shown resistance. As much as 92.7% of E. coli isolates had experienced Multi-Drug Resistance (MDR), which showed AMR to more than two antibiotic groups. The risk factor of farmer knowledge about AMR was associated with the MDR of E. coli. AMR requires the coordination of the stakeholders to carry out socialization and educate farmers in providing appropriate knowledge and using antibiotics wisely.